Renal Hypoxia in CKD; Pathophysiology and Detecting Methods - Hirakawa, Yosuke; Tanaka, Tetsuhiro; Nangaku, Masaomi (Frontiers in Physiology, 2017)
Chronic kidney disease (CKD) is a major public health problem. Accumulating evidence suggests that CKD aggravates renal hypoxia, and in turn, renal hypoxia accelerates CKD progression. To eliminate this vicious cycle, hypoxia-related therapies, such as hypoxia-inducible factor (HIF) activation (prolyl hydroxylase domain inhibition) or NF-E2-related factor 2 activation, are currently under investigation. Clinical studies have revealed heterogeneity in renal oxygenation; therefore, the detection of patients with more hypoxic kidneys can be used to identify likely responders to hypoxia-oriented therapies. In this review, we provide a detailed description of current hypoxia detection methods. HIF degradation correlates with the intracellular oxygen concentration; thus, methods that can detect intracellular oxygen tension changes are desirable. The use of a microelectrode is a classical technique that is superior in quantitative performance; however, its high invasiveness and the fact that it reflects the extracellular oxygen tension are disadvantages. Pimonidazole protein adduct immunohistochemistry and HIF activation detection reflect intracellular oxygen tension, but these techniques yield qualitative data. Blood oxygen level-dependent magnetic resonance imaging has the advantage of low invasiveness, high quantitative performance, and application in clinical use, but its biggest disadvantage is that it measures only deoxyhemoglobin concentrations. Phosphorescence lifetime measurement is a relatively novel in vivo oxygen sensing technique that has the advantage of being quantitative; however, it has several disadvantages, such as toxicity of the phosphorescent dye and the inability to assess deeper tissues. Understanding the advantages and disadvantages of these hypoxia detection methods will help researchers precisely assess renal hypoxia and develop new therapeutics against renal hypoxia-associated CKD.